Municipal solid waste composition in Maran, Pahang (Malaysia) landfills / Siti Suhaila Harith ...[et al.] - Harith, Siti Suhaila; Ramlan, Mohd Noor; Kassim, Hafizah; Shahul Hamid, Fauziah (2005)
In Malaysia, 0.7 to 1.2 kg per capita of municipal solid waste is generated and sent to 144 landfills throughout the country for disposal. The landfills could only cope with the current waste generation of 1.07 million tonnes per year. Due to rapid urbanization, active landfills would be running out of space as a result of the increment of waste volume. This study was conducted to compile data and collect the necessary information from selected landfills in Maran, Pahang, Malaysia. The landfills involved in this study are Jengka 10 landfill (Open dumping) and Batu 55 landfill (Upgraded landfill). The wastes were sorted into paper, putrescible waste, textile, metal, non metal, glass, plastic, rubber, wood, disposable diapers, aluminum and others items for quantification. Putrescible waste (on fresh weight basis) ranged.from 11% to 47% in Jengka 10 landfill, whereas in Batu 55 landfill it ranged from 27% to 31%. The average percentage was approximately 28% from both landfills. The average percentages of paper received by Jengka 10 and Batu 55 landfills were 18% and 22%, respectively. The average percentages of plastic separated at both landfills were 13% and 32%, respectively, while metal ranged from 3% to 6%. The average percentages of rubber waste disposed at the landfills were 9% and 10%, respectively. Disposable diapers contributed up to 4% of the total waste received at both landfills. Since both landfills are receiving extremely heterogeneous mixture of waste ranging from recyclable plastic and papers and others, it calls for a need of an integrated waste management system to optimize resource recovery.